2018
DOI: 10.1002/we.2222
|View full text |Cite
|
Sign up to set email alerts
|

Multiline anchor force dynamics in floating offshore wind turbines

Abstract: Floating offshore wind energy has seen significant progress, evidenced by multiple demonstration projects and the first floating wind farm (Hywind Scotland). However, the high capital cost associated with floating wind development remains one of the primary hurdles in the industry's growth. In efforts to lower this cost, this paper investigates a novel shared anchor concept to reduce the total number of anchors and installations. Two different multiline geometries are studied-a 3-line anchor system and a 6-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 15 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The cost of geo-technical investigations is a function of water depth, site conditions, preexisting survey data and method of investigation. The geo-technical site investigation costs are also dependent on the number of anchors (Fontana (2019)). In a wind farm with shared anchors, there is a significant reduction in the number of anchors.…”
Section: Shared Mooring and Anchoring Systemsmentioning
confidence: 99%
“…The cost of geo-technical investigations is a function of water depth, site conditions, preexisting survey data and method of investigation. The geo-technical site investigation costs are also dependent on the number of anchors (Fontana (2019)). In a wind farm with shared anchors, there is a significant reduction in the number of anchors.…”
Section: Shared Mooring and Anchoring Systemsmentioning
confidence: 99%
“…It is also vital that cost reduction of mooring system builds on reasonable distance between floating offshore wind turbines. In Casey's research [8,9], the NREL 5MW wind turbine on OC4 semi-submersible…”
Section: Space Optimization Of Multiline Anchors and Shallow Water Mo...mentioning
confidence: 99%
“…This would help to bring down geo-technical site investigation costs. (Fontana (2019)) compared the costs of installation and geo-technical site investigation for different farm sizes. It was found that a multi-line configuration reduces the installation cost for wind farms with 36 or more wind turbines.…”
Section: Shared Mooring and Anchoring Systemsmentioning
confidence: 99%